ОПЫТ ЛЕЧЕНИЯ БОЛЬНОГО С ЭКССУДАТИВНЫМ ПЕРИКАРДИТОМ, ВОЗНИКШЕГО НА ФОНЕ КОЛОРЕКТАЛЬНОГО РАКА - Бойко В. В.; Тамм Т. И.; Бучнева О. В. (World Science, 2019)
In the article presented the results of the treatment of pericardial effusion in a patient with sigmoid colon cancer. The pathological process in the pericardial cavity was asymptomatic and was discovered as an accidental find during a preoperative examination before surgery on the abdominal organs. The importance of timely diagnosis of such a serious and rare complication is shown. The presence of pericardial effusion in a patient with colorectal cancer changed the treatment tactics and forced to shift the focus of surgical interventions. This helped to reduce the risk of major surgical intervention on the abdominal organs and a favorable outcome for the patient.